2004
DOI: 10.1055/s-2003-44965
|View full text |Cite
|
Sign up to set email alerts
|

Corannulene Polysulfides: Molecular Bowls with Multiple Arms and Flaps

Abstract: Nucleophilic aromatic substitution of all the chlorine atoms in 1,3,5,7,9-pentachlorocorannulene and in decachlorocorannulene by sodium alkanethiolates gives 1,3,5,7,9-pentakis(1-alkylthio)corannulenes, C 20 H 5 (SR) 5 , and decakis(1-alkylthio)corannulenes, C 20 (SR) 10 , respectively, with arms of varying lengths attached around the perimeter (R = n-propyl, n-hexyl, and ndodecyl). The corresponding reaction of decachlorocorannulene with ortho-C 6 H 4 (SNa) 2 gives pentakis(1,4-benzodithiino)corannulene, a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…It is known that the presence of heteroatoms perturbs the electronic properties of the whole carbon/hydrogen system in terms of electrostatics and frontier orbitals energy levels. , In fact, corannulene chalcogenides, especially sulfur-derived corannulene compounds, are among the most studied given the possibility of fine-tuning their properties depending on the number of substituents, the location of the heteroatom and its oxidation state. Scott and co-workers pioneered the host–guest chemistry of sulfur-derived corannulenes with fullerenes obtaining moderate binding affinities, but overall outstanding considering there was only one corannulene core instead of a tweezer-like arrangement. According to their results, they concluded that the relative electron-rich orthophenylene substituents definitely contributed to the association enhancement, especially for their fly trap host, albeit a possible increased fullerene surface coverage could have had a higher impact through attractive dispersion forces.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the presence of heteroatoms perturbs the electronic properties of the whole carbon/hydrogen system in terms of electrostatics and frontier orbitals energy levels. , In fact, corannulene chalcogenides, especially sulfur-derived corannulene compounds, are among the most studied given the possibility of fine-tuning their properties depending on the number of substituents, the location of the heteroatom and its oxidation state. Scott and co-workers pioneered the host–guest chemistry of sulfur-derived corannulenes with fullerenes obtaining moderate binding affinities, but overall outstanding considering there was only one corannulene core instead of a tweezer-like arrangement. According to their results, they concluded that the relative electron-rich orthophenylene substituents definitely contributed to the association enhancement, especially for their fly trap host, albeit a possible increased fullerene surface coverage could have had a higher impact through attractive dispersion forces.…”
Section: Introductionmentioning
confidence: 99%
“…Scott and co-workers have employed a combination of the two motifs to design hosts of fullerene C 60 . 47,48 The optoelectronic properties of the persulfurated corannulene derivatives and 10-fold sulfuration of the corannulene nucleus are described by Baldridge and Siegel. 49,50 In the present context, a single substitution of the corannulene nucleus with an ethylene glycol-based side chain was considered as the simplest amphiphilic structure with which the investigations into the aforementioned questions could begin.…”
Section: Resultsmentioning
confidence: 99%
“…This powerful nucleophile can then be used for a substitution reaction with halocorannulene to establish a thio–ether linkage between the hydrophobic core and the hydrophilic side chain. 47,49,50 In this way, the simplest amphiphilic structure 2 was prepared and isolated in an 80% yield. After achieving synthesis of 2 , an increase in the polar ethylene glycol arm length was considered.…”
Section: Resultsmentioning
confidence: 99%
“…Following the initial results, Scott extended his investigations by synthesizing a library of penta‐ and decasubstituted corannulenes ( 8 c – d and 10 – 11 ) decorated with alkyl/arylthio groups in 2004 (Scheme 2–3). [16] A year later, fullerene association studies of the two derivatives: pentakis(propylthio)corannulene 8 c and pentakis(1,2‐benzodithio)corannulene 11 were presented [17] . Due to the low solubility of these compounds in toluene, the association was investigated in a mixture of CS 2 and dimethylsulfoxide (DMSO).…”
Section: Discussionmentioning
confidence: 99%